2006
DOI: 10.1002/jmri.20766
|View full text |Cite
|
Sign up to set email alerts
|

Open‐chest 31P magnetic resonance spectroscopy of mouse heart at 4.7 Tesla

Abstract: Purpose: To develop a rapid, robust, and accurate method for assessing myocardial energetics in mice and demonstrate its applicability to mouse models of acquired and genetic heart disease. Materials and Methods:We combined surface coil localization (10-mm diameter, tunable between 1 H and 31 P, using adiabatic half-passage radiofrequency pulses) and surgery (electrocautery removal of anterior chest wall) to create an open-chest method for acquiring in vivo 31 P nuclear magnetic resonance (NMR) cardiac spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Our previous study demonstrated that myocardial energetic defect and myocardial FAO depression were the main features of mice with cardiomyocyte-restricted PPARδ deficiency (CR-PPARδ −/− ) [20] [25]. To investigate cardiac Mfn2 expression in CR-PPARδ −/− hearts, expression levels of Mfn2 genes were evaluated by Real Time PCR measurement on RNA samples from CR-PPARδ −/− and control mice before overt phenotypic changes.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that myocardial energetic defect and myocardial FAO depression were the main features of mice with cardiomyocyte-restricted PPARδ deficiency (CR-PPARδ −/− ) [20] [25]. To investigate cardiac Mfn2 expression in CR-PPARδ −/− hearts, expression levels of Mfn2 genes were evaluated by Real Time PCR measurement on RNA samples from CR-PPARδ −/− and control mice before overt phenotypic changes.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that PPARδ is required for normal transcript expression of series essential enzymes that govern myocardial FAO in the long-term cardiomyocyte-restricted PPARδ knockout (CR-PPARδ −/− ) mouse model3, These mice exhibited depressed myocardial FAO and bioenergetics, eventually leading to dilated cardiomyopathy with myocardial lipid accumulation in adult and older mice3, 9. The gene knockout event in the CR-PPARδ −/− mice, mediated by α-MyHC-driven expression of Cre recombinase, is expressed in ventricles during early development and robustly from new born stage.…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, the three subtypes of PPARs, PPARα, γand δ are expressed at various levels and play important roles in myocardial lipid and glucose metabolisms17. We have demonstrated that PPARδ is required for normal transcript expression of series essential enzymes of fatty acid oxidation (FAO) in the heart and that cardiomyocyte-restricted PPARδ knockout resulted in depressed myocardial FAO and bioenergetics, cardiac hypertrophy and heart failure8, 9. Furthermore, there is emerging evidence demonstrating that PPARs may play a role in regulating transcriptional expression of antioxidants, such as Cu/Zn-Superoxide dismutase (SOD1) 10, manganese superoxide dismutase (SOD2)11, 12, and catalase1315.…”
Section: Introductionmentioning
confidence: 99%
“…4, 7, 8 Long-term, postnatal, cardiomyocyte-restricted PPARβ/δ deletion in mice perturbs myocardial fatty acid oxidation (FAO) and leads to cardiac dysfunction, bioenergetic defect, cardiac hypertrophy and lipotoxic cardiomyopathy. 4, 9 We have recently discovered that PPARβ/δ is essential for the adult heart to maintain mitochondrial capacity and oxidative metabolism. 10 However, little is known about the gain-of-function effects of PPARβ/δ activation in the adult heart.…”
Section: Introductionmentioning
confidence: 99%